Microbiological Contamination and Hydrocarbon Pollution of Surface Water and Sediments in the Okulu River, Rivers State, Nigeria - Chukwudozie Colman Ifiora; G. N. Woke; Felicity Uju Onwudinjo; Chimezie Ekeke; T. M. Iringe-Koko; Paul Aforji Osaro (Journal Majelis Paspama, 2026)
Surface water bodies in industrialized regions are increasingly threatened by microbiological contamination and hydrocarbon pollution, raising serious concerns for environmental sustainability and public health The study employed a field-based analytical design to evaluate microbiological and physicochemical contamination of surface water and sediments in the Okulu River. Five sampling stations were established, comprising four industrially impacted sites and one control site. Surface water and sediment samples were systematically collected, preserved, and analyzed for total coliforms, Escherichia coli, petroleum aromatic hydrocarbons, and potassium using standard laboratory techniques. Results were statistically analyzed and compared with World Health Organization standards to assess contamination levels, spatial variation, and associated environmental and public health risks. Results revealed marked spatial variation and widespread contamination of the Okulu River. Total coliforms in surface water exceeded WHO limits at all stations, peaking at SW4 (712 cfu/100 ml) compared to the control (0.01 cfu/100 ml). Sediments showed even higher coliform loads, with SD4 recording 7,765 cfu/100 ml. E. coli counts followed similar trends in surface water (SW4: 84.2 cfu/100 ml) and sediments (SD4: 903.5 cfu/100 ml), indicating fecal pollution. PAH concentrations were extremely elevated in surface water (SW4: 1,723 ppm) and sediments (SD4: 2,606 ppm), far above WHO limits. Potassium exceeded guidelines in impacted sites for water (up to 17.02 mg/L) and sediments (up to 84.08 mg/L). In conclusion, the Okulu River is severely degraded by combined microbiological and hydrocarbon pollution, posing significant ecological and public health risks and necessitating urgent regulatory enforcement, continuous monitoring, and remediation interventions.